X-Ray Study of Synthesized Clinkers - Egamberdiev M.S. (Zien Journals, 2023)
X-ray examination made it possible to establish that the specified minerals were formed in the process of obtaining clinkers. At the same time, it was revealed that excess calcium sulfate contributes to the stabilization of the mineralogical composition.
Keywords: sulfosilicate; sulfoaluminate; X-ray phase analysis